Analysis Regarding Brand Dispute Cases Based on Case Study of Decision Number 4 Pk/Pdt.Sus-Hki/2023 - Jeane Neltje Saly; Ivana Trixie; Margaretha Putri; Pricillia Imanuela; Angeline Wellvy Santoso (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Brand is a very important thing for the business world, especially for business people, because the brand is the identity of a product or company that is very valuable. A well-known brand from the United States, namely TIMBERLAND, is in dispute with a local brand, namely TIMBERLAKE, judging from the sentence that dominates the word "TIMBER" and from its mention it can confuse consumers. The registration of the TIMBERLAKE trademark had bad faith and wanted to piggyback on the well-known American brand, TIMBERLAND, because there were similarities in the marks that were detrimental to the plaintiff.